Replacement of Metaphylactic Antimicrobial Therapy by Oral Administration of Ligilactobacillus salivarius MP100 in a Pig Farm - Sobrino, Odón J.; Alba, Claudio; Arroyo, Rebeca; Pérez, Inés; Sariego, Lydia; Delgado, Susana; Fernández, Leónides; de María, Julián; Fumanal, Pilar; Fumanal, Antonio; Rodríguez, Juan M. (Frontiers in Veterinary Science, 2021)
Antibiotic use in swine production contributes to the emergence and spread of resistant bacteria, which poses a threat on human health. Therefore, alternative approaches must be developed. The objective of this work was the characterization of the probiotic properties of a Ligilactobacillus salivarius strain isolated from sow's milk and its application as an inoculated fermented feed to pregnant sows and piglets. The study was carried in a farm in which metaphylactic use of antimicrobials (including zinc oxide) was eliminated at the time of starting the probiotic intervention, which lasted for 2 years. Feces from 8-week-old piglets were collected before and after the treatment and microbiological and biochemical analyses were performed. The procedure led to an increase in the concentrations of clostridia and lactobacilli-related bacteria. Parallel, an increase in the concentration of butyrate, propionate and acetate was observed and a notable reduction in the presence of antibiotic resistant lactobacilli became apparent. In conclusion, replacement of antimicrobials by a microbiota-friendly approach was feasible and led to positive microbiological and biochemical changes in the enteric environment.